Immunohistochemistry and Next-generation Sequencing Are Complementary Tests in Identifying PTEN Abnormality in Endometrial Carcinoma Biopsies. (January 2022) - Wang, Linyuan; Piskorz, Anna; Bosse, Tjalling; Jimenez-Linan, Mercedes; Rous, Brian; Gilks, C. Blake; Brenton, James D.; Singh, Naveena; Köbel, Martin
Abstract : PTEN plays a central role in the pathogenesis of endometrial carcinoma. Previous studies reported a high interobserver reproducibility for the interpretation of PTEN immunohistochemistry (IHC). However, PTEN IHC and its interpretation remain challenging during laboratory practice. The purpose of this study was to reevaluate PTEN IHC pattern in direct comparison to next-generation sequencing in identifying PTEN abnormality. IHC and tagged-amplicon next-generation sequencing PTEN sequencing was performed on 182 endometrial carcinoma biopsy/curetting samples from five centers (Barts, Calgary, Cambridge, Leiden, and Vancouver). Sensitivity, specificity and accuracy of PTEN IHC to predict loss of function PTEN mutations were calculated. Abnormalities of PTEN in association with histotype and molecular subtype were assessed. A total of 5 PTEN IHC patterns were recorded: absent, subclonal loss, equivocal, reduced (relative to internal control) and retained. The absence of PTEN IHC has a sensitivity of 75.4% (95% confidence interval: 62.7–85.5%), a specificity of 84.6% (95% confidence interval: 76.2%–90.9%), and accuracy of 81.2% (95% confidence interval: 74.4%–86.9%) in predicting loss of function PTEN mutation. PTEN abnormality by complementary interpretation of both assays was present in 91.9% of endometrial endometrioid carcinoma, grade 1, and significantly higher in endometrial endometrioid carcinomas of all grades compared with endometrial serous carcinoma (80.0% vs. 19.4%, P <0.0001). PTEN abnormalities are common across all molecular subtypes of endometrioid carcinomas. Our data support the use of ancillary PTEN IHC for diagnostic purposes in endometrial neoplasms. However, for clinical trial design complementary testing of both IHC and sequencing of PTEN should be considered to assess the PTEN status in endometrial carcinomas.